Efforts to Reform Law Enforcement in Tackling Cybercrime - Dewi Suryandari, Wieke (Yayasan Meira Visi Persada, 2024)
Cybercrime in Indonesia has risen significantly, posing threats to personal data security and critical information systems. The Electronic Information and Transactions Law (UU ITE) provides a legal framework for addressing cybercrime by imposing criminal sanctions on offenders. The UU ITE covers various aspects, including personal data protection, online fraud, hacking, and malware dissemination. While UU ITE offers a solid legal foundation, challenges remain ineffective implementation and enforcement. Therefore, it is crucial to continuously update and strengthen regulations and enforcement mechanisms to effectively tackle increasingly complex cyber threats in the digital age.